Metode Pendekatan Tafsir Kontekstual Prespektif Fazlur Rahman - Kholifatin, Luluk Indah (Journal of Islamic Education, 2025)
This study aims to analyze Fazlur Rahman's contextual interpretation method, known as the "Double Movement" approach, in bridging the teachings of the Qur'an with the needs of the modern era. The research employs a historical-critical method, linking the social, cultural, and historical contexts of revelation with the application of moral values in contemporary times. The findings reveal that this method, through its two main stages analyzing the historical context of revelation and applying moral principles to the present effectively provides a more relevant understanding of the Qur'anic teachings. Examples of its application to issues such as the prohibition of alcohol and polygamy underscore the importance of a gradual approach in addressing the social conditions of the time when the revelations were revealed. Fazlur Rahman also emphasizes the necessity of integrating theology, ethics, and law to address modern challenges without losing the essence of the Qur'an's universal values. The study concludes that this method offers an interpretation that is progressive, just, and aligned with contemporary developments.